Exploring the population ecological characteristics and the stock status of mitre squid (Uroteuthis chinensis Gray, 1849) in Belitung waters, Indonesia - R. Kurniawan; Tirtadanu; R. Puspasari; M. R. A. Putri; K. Amri; A. Rahman; Y. Sugianti; Mujiyanto; P. Lestari; K. Wagiyo (Brazilian Journal of Biology)
Abstract The intensive fishing and lack of data for squid fisheries in Belitung waters have increased the risk of stock population decline, which could lead to large economic losses. Comprehensive studies on the biological aspects and stock status of squid were crucial to developing some management recommendations. This study investigated several population ecological characteristics (size distribution, length-weight relationship, condition factors, maturity stages, length at maturity, and growth parameters), the stock status, and the biological reference points of mitre squid (Uroteuthis chinensis Gray, 1849) in Belitung waters. The squid’s biological data were collected from August 2023 to March 2024. The stock status was investigated by several approaches, including length-converted catch-curve (LCC), yield per recruit (YPR) analysis, and length-based spawning potential ratio (LB-SPR). This study revealed that the mean size of male and female squid captured by squid jig was 16.22 ± 6.72 cm and 14.23 ± 3.65 cm (Mean of mantle length ± standard deviation), with the length at first maturity (Lm50) of 19 cm for males and 12 cm for females. Female gonadally mature squid were found throughout the year, with the largest proportion in January (93%). The overfishing condition of U. chinensis has occurred based on the current exploitation level for male (Ecur: 0.63; Fcur: 2.61 year-1) and female (Ecur: 0.72; Fcur: 4.39 year-1) that exceeds both the optimal exploitation rate (Eopt=0.5) and the fishing mortality given the maximum yield per recruit (Male Fmax: 2.08 year-1; Female Fmax: 3.35 year-1). Recruitment overfishing has also occurred based on the current spawning potential ratio of 18%. Reducing the fishing trips by 24%, applying a season closure in January, and enlarging the selectivity to 15 cm were recommended to raise the squid stock and ensure the sustainability of squid fisheries in Belitung waters.